LANGUAGE REPRESENTATION OF GENDER AND AGE FEATURES OF THE CONCEPT “BEAUTY” IN ENGLISH COSMETICS ADVERTISING TEXTS - Kozyr, Yelyzaveta (Scientific Journal of Polonia University, 2025)
This article concerns the representation of the concept of beauty in English-language adverts throw the English-language cosmetic adverts. The article contains the results of the research of theoretic and practical materials. On the basis of the research the author shows that the study of the linguistic aspects of advertising is attractive from the point of science, because advertisement is an integral part of modern life. Language means play a crucial role in the shaping stereotypes within cultural groups. The present study addresses the issues of gender neutralization in English-language advertising and newspaper texts. The paper investigates linguistic means involved in the creation of gender- neutral advertising texts. As a result of the study, we conclude that the main features of gender-neutral advertising texts are the absence of lexical units that would refer advertising to male or female; the use of scientific terms, numbers in the description of the goods; the use of imperative sentences. Gender neutralization in advertising occurs due to the use of impersonal sentences, defining pronouns and euphemisms. Gender neutralization is a relatively new trend in advertising and has a huge impact on the use of language in modern advertising texts. Linguistic selection in advertising, especially the focus on gendered language, is the main concern in this study. The main concentration in the research is the investigation into the use of specific verbal items in commercials to confirm the idea that there are differences among adverts of similar products for either male or female consumers. The result of this paper can partly contribute to industrial areas as well as other academic fields such as sociolinguistics.